Analysing the experiences of Zimbabwean migrants in acquiring the Zimbabwean special permit - Skota, Siyamthanda (My University, 2020)
‘This qualitative study uses a phenomenological methodology to analyse ten Zimbabwean migrants’ experiences in acquiring the Zimbabwean Special Permit (ZSP) since its inception in 2010,with the human rights of applicants as a guiding concern. The study utilises ten semi-structured in-depth interviews with Zimbabwean migrants who are on the work permit category of the ZSP, a representative of the Department of Home Affairs (DHA), and an official representing the Zimbabwean community at African Diaspora Forum. After coding and analysing the data according to research questions, literature and theoretical framework used in the study, three broad themes emerged from migrants’ experiences: 1) employment and financial freedom; 2) freedom of movement; 3) documentation. Even though administrative challenges with the DHA were intense in 2009, they have improved over the years mainly because of the move from manual applications to online applications. After acquiring the ZSP migrants’ expressed gratitude because they are now able to look for legal work and manage their finances. Secondly, the ZSP holders can now exercise their most basic human right which is the right to freedom of movement. And finally, the Zimbabwean migrants are concerned about what the future holds for their documentation status in South Africa, with pleas for permanent residence’
The experiences of Zimbabwean immigrants in acquiring the Zimbabwean special permits
A research report submitted to the Faculty of Management, University of the Witwatersrand, in 50% requirement for the degree of Master of Management (In the field of Public Policy), 2020
Keywords: UCTD; ZIMBABWEAN MIGRANTS; IMMIGRATION; PERMITS; SDG-10: Reduced inequalities